Perceptions and The Implementation of Continuing Professional Development Through Publication Among English Teachers - Kasprabowo, Teguh; Sofwan, Ahmad; Bharati, DwiAnggani Linggar (Universitas Negeri Semarang, 2018)
This article is part of bigger study aiming to investigate Junior High School English teachers’ perceptions of continuing professional development (CPD) and its scheme implementation through self-development, publication and innovation. This article highlights the implementation of CPD through publication. The study employed qualitative method The data was first obtained from the questionnaire distributed to 13 English teachers. The result of the data was presented in simple percentage. Later, to get deeper understanding 7 English teachers were selected conveniently out of the 13 teachers to be interviewed. Data analysis of CPD implementation of the teachers is used as the evidence of the practice. The findings showed that English teachers in this study had positive perceptions towards CPD scheme implementation through publication. In practice, however, only few teachers wrote or published their works. This condition was caused by the limited time of the teachers to write, the lack of training on writing and other responsibilities besides teaching they had to bear. To help teachers publish their works, assistant in the form of training by experts is needed. Teachers’ active participation in teachers’ forums helping them to write should also be encouraged.